Reduction of Orexin-A Is Associated With Anxiety and the Level of Depression of Male Methamphetamine Users During the Initial Withdrawal Period - Guo, Lei; Hu, Aqian; Zhao, Xiaoxi; Xiang, Xiaojun (Frontiers in Psychiatry, 2022)
Background: Orexin has been linked to the regulation of reward and motivation in animals, but there have been few human studies to validate its regulatory effects. We aimed to determine how orexin-A levels changed during different stages of withdrawal, as well as the relationship between orexin-A levels and withdrawal symptoms in male METH users. Methods: This study included 76 METH users and 35 control participants. The METH users were divided into three groups: group 1 (abstinence within 1 week, n=23), group 2 (abstinence between 1 week and 3 months, n=38), and group 3 (abstinence over 3 months, n=15). At baseline and one month later, the plasma orexin-A level was examined. To track the withdrawal signatures, self-report questionnaires (anxiety, depression, desire, and sleep quality) were collected at two points. Results: The orexin-A levels of groups 1 (p<0.00) and 2 (p<0.00) were lower than that of the controls at baseline but not group 3. One month later, the orexin-A levels of group 2 (p<0.05) significantly increased, while no significant changes in those of groups 1 and 3 were observed. Furthermore, the orexin-A levels of group 1 were positively linked with depression (p<0.05) and anxiety (p<0.05) at baseline. Conclusions: The decrease in orexin-A levels was only transitory during the initial abstinence phase, and it was eventually restored near to normal with continued abstinence of the male METH users. Furthermore, a lower concentration of orexin-A may serve as a risk factor for negative emotions during METH withdrawal.